New approaches to study canine and equine influenza A virus - Leverett, H.E. (2025)
Equine and canine influenza A viruses (IAV) have been isolated for the past 70 and 25 years, respectively. Currently, a single subtype of equine influenza A virus (H3N8) circulates. This subtype jumped species to canines in the late 1990s in the US and circulated until 2016. In 2004, an avian H3N2 subtype virus was transmitted to dogs and spread into the US where it continues to circulate. Limited research is ongoing to further understand these two neglected viruses although within the research community, new approaches are more often applied to emerging and human influenza viruses. In this research, how novel approaches can be used to generate reagents and further develop the understanding of these two viruses was investigated.